The Effect of Project Based Learning on Students’ Motivation and Learning Outcomes at SMP Negeri 1 Sape - Murtalib, Murtalib; Mutmainah, Mutmainah; Mikrayanti, Mikrayanti (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study aims to determine the effect of student motivation and learning outcomes by using the Project Based Learning at SMP Negeri 1 Sape. The research method that will be used in this study is a quasi-experimental research with a descriptive quantitative approach. The research design uses the Posttest Only Control Group Design form, the sample to be used in this study consists of two classes, namely the VIIIA experimental class of 25 students and the VIIIB Control Class of 28 students. The types of instruments used in this study are questionnaires and learning outcomes tests. Data analysis in this study used prerequisite tests, namely normality test, homogeneity test. To test the correctness of the hypothesis, the help of statistical analysis of ManovaSPSS v.22.0 was used.Based on hypothesis testing using the SPSS v.22 Manova test, it is known that the value of learning outcomes Sig. 0.081 or 0.081˃0.05, it can be concluded that titung˂ttabel then H0 is accepted and Ha is rejected. Likewise, in the learning motivation hypothesis test there is a sig value. 0.369 or 0.369˃0.05 which means H0 is accepted and Ha is rejected. Thus it can be concluded that there is no difference in the effect of motivation and learning outcomes of students taught using the Project Based Learning learning model in the experimental class and students taught using conventional learning in the control class. This study aims to determine the effect of student motivation and learning outcomes by using the Project Based Learning at SMP Negeri 1 Sape. The research method that will be used in this study is a quasi-experimental research with a descriptive quantitative approach. The research design uses the Posttest Only Control Group Design form, the sample to be used in this study consists of two classes, namely the VIIIA experimental class of 25 students and the VIIIB Control Class of 28 students. The types of instruments used in this study are questionnaires and learning outcomes tests. Data analysis in this study used prerequisite tests, namely normality test, homogeneity test. To test the correctness of the hypothesis, the help of statistical analysis of ManovaSPSS v.22.0 was used.Based on hypothesis testing using the SPSS v.22 Manova test, it is known that the value of learning outcomes Sig. 0.081 or 0.081˃0.05, it can be concluded that titung˂ttabel then H0 is accepted and Ha is rejected. Likewise, in the learning motivation hypothesis test there is a sig value. 0.369 or 0.369˃0.05 which means H0 is accepted and Ha is rejected. Thus it can be concluded that there is no difference in the effect of motivation and learning outcomes of students taught using the Project Based Learning learning model in the experimental class and students taught using conventional learning in the control class. This study aims to determine the effect of student motivation and learning outcomes by using the Project Based Learning at SMP Negeri 1 Sape. The research method that will be used in this study is a quasi-experimental research with a descriptive quantitative approach. The research design uses the Posttest Only Control Group Design form, the sample to be used in this study consists of two classes, namely the VIIIA experimental class of 25 students and the VIIIB Control Class of 28 students. The types of instruments used in this study are questionnaires and learning outcomes tests. Data analysis in this study used prerequisite tests, namely normality test, homogeneity test. To test the correctness of the hypothesis, the help of statistical analysis of ManovaSPSS v.22.0 was used.Based on hypothesis testing using the SPSS v.22 Manova test, it is known that the value of learning outcomes Sig. 0.081 or 0.081˃0.05, it can be concluded that titung˂ttabel then H0 is accepted and Ha is rejected. Likewise, in the learning motivation hypothesis test there is a sig value. 0.369 or 0.369˃0.05 which means H0 is accepted and Ha is rejected. Thus it can be concluded that there is no difference in the effect of motivation and learning outcomes of students taught using the Project Based Learning learning model in the experimental class and students taught using conventional learning in the control class.